A Generalized Gazi-Passino model with coordinate-coupling matrices for swarm formation with rotation behavior - GAZİ, VEYSEL (My University, 2022)
In this article, a kinematic continuous time swarm model is considered by extending the results in the paper \"A class of attractions/repulsion functions for stable swarm aggregations\" (as shown in the International Journal of Control, vol. 77, pages 1567-1579). The extension regards a more general class of attraction/repulsion functions that can be used to explain the formation of rotational patterns in a swarm of agents. The main characteristic of this model is the introduction of two coordinate-coupling matrices weighting both the attractive and the repulsive interactions among the agents. A stability analysis is presented to characterize the swarm in terms of size and cohesiveness. Moreover, a class of attraction/repulsion functions is presented to guarantee the cohesiveness of the swarm in a polytopic region and a steady-state motion of the agents in a rotational frame around the swarm centroid. Numerical simulations are provided to illustrate the obtained results.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Bilgisayar Bilimleri; Bilgi Güvenliği ve Güvenilirliği; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Computer Sciences; Information Security and Reliability; Engineering and Technology; OTOMASYON & KONTROL SİSTEMLERİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); BİLGİSAYAR BİLİMİ, BİLGİ SİSTEMLERİ; Bilgisayar Bilimi; AUTOMATION & CONTROL SYSTEMS; ENGINEERING; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE, INFORMATION SYSTEMS; COMPUTER SCIENCE; Kontrol ve Optimizasyon; Genel Mühendislik; Mühendislik (çeşitli); Bilgi sistemi; Bilgisayar Bilimi Uygulamaları; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Fizik Bilimleri; Control and Optimization; General Engineering; Control and Systems Engineering; Engineering (miscellaneous); Information Systems; Computer Science Applications; Computer Science (miscellaneous); General Computer Science; Physical Sciences